If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y in (-oo:+oo)
(-3/2)*y = (-9/4)*y+4/3 // - (-9/4)*y+4/3
(-3/2)*y-((-9/4)*y)-(4/3) = 0
(-3/2)*y+(9/4)*y-4/3 = 0
3/4*y-4/3 = 0 // + 4/3
3/4*y = 4/3 // : 3/4
y = 4/3/3/4
y = 16/9
y = 16/9
| 2/3(1/2x+2/5)=1/2(5/6x-2/3) | | 37=24-5r | | x+2y+9x-4y=4+3 | | 5b+11+2b=50 | | -2(t-2)-(t+7)=3 | | 8x+2=16x+3 | | 2y/5-3/4=0 | | Y-0=0(x-2) | | 3/2+11/8+5/4y=9/2y | | -4*m-3=54 | | 7y+4x=9 | | f+(vc)*q=(sp)*q | | 3/2+11/8+5 | | -4+5y/4=5/3 | | 8/2.8 | | -2(3x-10)=20 | | 1/5y-5=7 | | 6.35=7+x | | 2m-(m+10)=0 | | 4x-(x+1)=x-(x-5) | | 1/4=-x+8/5 | | 6+40=210 | | -1+8y/5=-5/3-y+3y/5 | | 9.5x+3=5.5x+4 | | (4/5)+(2/7)= | | 30z+(27z-5)=-28 | | 17/9= | | 17x-(5x-9)=21 | | -1+y/3=0 | | 3(x)-8=100 | | 6y+3x=15 | | 11y-12/8+3y/5=6y-1/8 |